Edukasi Kesehatan Mental melalui Video Animasi sebagai Upaya Peningkatan Pengetahuan Remaja - Riska Saputri; Noor Yunida Triana; Ikit Netra Wirakhmi (Yayasan Inspirasi El Burhani, 2026)
Introduction: Mental health is an important aspect of adolescent development that affects physical, emotional, and social well-being. Adolescents are vulnerable to mental health problems due to academic pressure, social challenges, and developmental changes, while students at SMK Negeri 1 Bukateja were found to have limited understanding of basic mental health concepts. Objective: The purpose of this service was to increase adolescents’ knowledge and awareness of mental health through educational interventions using animated video media. Method: This public service was conducted among 35 students of class XI DPB 2 at SMK Negeri 1 Bukateja using animated videos supported by lectures and discussions, with a pretest–posttest design to evaluate knowledge improvement. Result: The results showed a significant increase in students’ knowledge after the educational intervention. Before the program, 11.42% of students had poor knowledge, 51.42% had moderate knowledge, and 37.14% had good knowledge. After the intervention, the proportion of students with good knowledge increased to 88.57%, while 11.42% remained in the moderate category, and none were classified as having poor knowledge. Conclusion: Mental health education delivered through animated video media was effective in improving adolescents’ knowledge and supporting mental health awareness in the school setting.